PHD finger protein 5A promoted lung adenocarcinoma progression via alternative splicing. (1st April 2019) - Mao, Shuangshuang; Li, Yuan; Lu, Zhiliang; Che, Yun; Huang, Jianbing; Lei, Yuanyuan; Wang, Yalong; Liu, Chengming; Wang, Xinfeng; Zheng, Sufei; Sun, Nan; He, Jie
Abstract: Alternative splicing (AS) and the regulation of AS by splicing factors play critical roles in cancer. Plant homeodomain (PHD)–finger domain protein PHF5A, a critical splicing factor involved in AS, has been demonstrated to play an oncogenic role in glioblastoma multiforme and breast cancer, but its biological function in lung cancer remains unclear. In the present study, we systematically analyzed the biological function and clinical relevance of PHF5A in non–small cell lung cancer (NSCLC). We found that PHF5A was significantly upregulated in NSCLC tumors compared with normal tissues in both TCGA data set and tissue microarrays. Upregulation of PHF5A was negatively correlated to the overall survival (OS) of lung adenocarcinoma (LUAD) patients. Loss‐of‐function and gain‐of‐function experiments confirmed that PHF5A functioned as an oncoprotein by promoting LUAD cell proliferation, migration and invasion, inducing G0/G1 cell cycle progression and inhibiting cisplatin–induced apoptosis. RNA–seq analysis identified many essential genes whose AS was dysregulated by PHF5A, including cell cycle–associated genes such as SKP2, CHEK2, ATR and apoptosis–associated genes such as API5 and BCL2L13. Additionally, pladienolide, a small molecular inhibitor of PHF5A, inhibited LUAD cell proliferation in a dose–dependent manner and induced AS changes similar to PHF5A knockdown. In conclusion, we validated that PHF5A played an oncogenic role via AS in LUAD and suggested that PHF5A might serve as a potential drug target with a promising anticancer therapeutic effect. Abstract : We demonstrated that PHF5A acted as a key regulator in the AS of many essential genes to promote the development and progression of LUAD. PHF5A might serve as a potential drug target with a promising anticancer therapeutic effect in LUAD patients.